DESKRIPSI HASIL BELAJAR BANGUN RUANG SISI DATAR PADA PENERAPAN DIRECT INSTRUCTION DENGAN ALAT PERAGA DIKELAS VIII F MTS N 02 KOTA BENGKULU TAHUN AJARAN 2016/2017 - supriadi, ari; rusdi, Rusdi; maulidiya, Della (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2017)
The purpose of this study is to obtain a description of the results of learning materials wake up flat space on the application of direct instruction with props in class VIII F MTs N 02 Kota Bengkulu. The research method used is quantitative description. The subject of this research is 27 students of class VIII F MTs N 02 Kota Bengkulu even semester of academic year 2016/2017. The instrument used is a sheet of student learning outcomes consisting of 4 essay questions. Direct instructional instruction steps with orientation aids, presentation with props wake up flat side room, structured practice with props wake up flat space, practice under teacher guidance, and independent practice. The average score of each indicator about the student's work is: indicator 1 = 17,40 (good), indicator 2 = 25,85 (good), indicator 3 = 11,37 (good enough), indicator 4 = 11,12 ( Good enough), indicator 5 = 21.44 (good), indicator 6 = 15.44 (good), indicator 7 = 20.25 (good), indicator 8 = 18.29 (good), indicator 9 = 35.7 (Good), and indicator 10 = 45,4 (good).Keywords: descriptions of learning outcomes; Direct instruction; learning outcomes.